Detection and Partial Purification of a Natural Heparin Inhibitor from Hog Small Intestine - Gertler, Menard M; Chien, Mingjien; Yue, Robert H (Thrombosis and Haemostasis, 1979)
A natural occurring heparin inhibitor was detected and was partially purified from the mucosa of hog small intestine. The mucosa was homogenized and was extracted overnight in 0.15 M NaCl, 0.01 M imidazole, 0.001 M EDTA, pH 6.5. When the extract was made to 85% saturation in ammonium sulfate, a large quantity of heparin neutralizing activity was detected in the precipitate. Each small intestine contains approximately 35,000 units of heparin neutralizing activity. This heparin inhibitor was further purified by the procedures of zinc sulfate precipitation, ammonium sulfate fractionation, ethanol precipitation and heparin-sepharose chromatography. A 37 fold partial purification with 15% overall recovery was achieved to yield heparin inhibitor with specific activity of 50-65 units per mg of protein.